The ESA OCDS Project - Enhancing the Concurrent Design Concept - Ton, A.; Richardson, R.; Relvas, A.; Christiansen, T.; Haenisch, J.; Coutinho, C. (Proceedings of the 10th NASA-ESA Workshop on Product Data Exchange (PDE 2008), Noordwijk, Netherlands, 2008)
This paper describes the output of a multi-year project to build a cross industry concurrent design platform. The platform, known as the Open Concurrent Design Server (OCDS), was initially built to support the space mission feasibility analysis at the European Space Agency (ESA). The vision however was to build a platform that could support concurrent design across a broad range of complex engineering tasks from Shipbuilding to Oil & Gas exploration.